Validation of an instrument to measure tutor performance in promoting self-directed learning by using confirmatory factor analysis - Genoveva; Osval Antonio; Noemí (Investigación y Educación en Enfermería, 2016)
Objective. This work sought to validate and propose an instrument to measure the performance of tutors in promoting self-directed learning in students involved in processes of problem-based learning. Methods. Confirmatory factor analysis (CFA) was applied to validate the instrument composed of 60 items and six factors (self-assessment of learning gaps within the United Nations specific context: self-assessment, reflexion, critical thinking, administration of information, group skills), using a sample of 207 students from a total of 279, which comprise the student population of the Faculty of Nursing at Universidad de Colima in Mexico. (2007). Results. The CFA results demonstrated that the instrument is acceptable to measure performance of tutors in promoting self-directed learning, given that all the indicators, variances, covariances, and thresholds are statistically significant. Conclusion. The instrument permits obtaining students’ opinions on how much professors contribute for them to develop each of the 60 skills described in the scale. Lastly, the results could report if professors are placing more emphasis in some areas than in other areas they should address during the problem-based learning (PBL) process, or if definitely their actions are removed from the premises of PBL, information that will be useful for school management in decision making on the direction of teaching as a whole. How to cite this article: Amador G, Montesinos-López OA, Alcaráz N. Validation of an instrument to measure tutor performance in promoting self-directed learning by using confirmatory factor analysis. Invest Educ Enferm. 2016; 34(1): 74-83